Spark of life - Remarque, Erich Maria, 1898-1970. (Inc., New York : Appleton-Century-Crofts, 1952)
Novel of life and death in a Nazi concentration camp.
Translation of der Funke Leben.
Keywords: World War, 1939 -- 1945 -- Atrocities -- Fiction; Concentration camps -- Fiction